2022
DOI: 10.3390/su14138140
|View full text |Cite
|
Sign up to set email alerts
|

Large Wood Debris Contributes to Beach Ecosystems but Colombian Beachgoer’s Do Not Recognize It

Abstract: Large Woody Debris (LWD) accumulation serves essential ecological functions and benefits society’s coastal ecosystems (e.g., beaches). Thus far, the ecosystem services perspective has paid little attention to LWD. Therefore, we aim to contrast social perceptions on LWD and its ecological significance in Puerto Velero beach, Caribbean, Colombia. In consequence, the contribution of LWD to the conformation and creation of Puerto Velero beach was analyzed, as well as how beachgoers perceive the importance of LWD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 134 publications
0
1
0
Order By: Relevance
“…A study conducted by Rangel-Buitrago et al [62] indicated a density of 0.8 items•m −2 at a nearby tourist beach, while the wood on non-tourist beaches (where the timber is not removed periodically) was as high as 3.8 items•m −2 . In this Caribbean region, wood plays an important role in maintaining the beach by decreasing erosion [63]. However, most people ignore the importance of wood in these processes because of its una ractiveness on the beach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Rangel-Buitrago et al [62] indicated a density of 0.8 items•m −2 at a nearby tourist beach, while the wood on non-tourist beaches (where the timber is not removed periodically) was as high as 3.8 items•m −2 . In this Caribbean region, wood plays an important role in maintaining the beach by decreasing erosion [63]. However, most people ignore the importance of wood in these processes because of its una ractiveness on the beach.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our study highlights the impact of beach geomorphology, local oceanographic conditions, and anthropogenic activities on marine li er accumulation pa erns. For example, the Colombian Caribbean coast is influenced by longshore currents that carry substantial amounts of li er and wood from the Magdalena River [63] to Salgar Beach. In addition, the prevailing offshore winds play a crucial role in the distribution of marine li er along the beach, exacerbating contamination levels close to the strand line.…”
Section: Temporal and Spatial Variabilitymentioning
confidence: 99%
“…For this reason, we found valuable the results provided by InVEST and the water regulation index, which contrasted with expert-based consultation and community perceptions. This represents a normal aspect in ES valuation, which is juxtaposition of values ( Manzolli et al., 2022 ; Peck and Khirfan, 2021 ; Suarez et al., 2021 ). We are aware on the complexity of applying several methodological steps, however, PV studies should face this load because resources, time and skills are necessary ( Maydana et al., 2020 ; Lopes and Videira, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the community's perceptions of environmental quality and ecotourism in the swamp can be very insightful for developing the activity. Thus, perceptions about environmental quality could determine the values people might give ecosystems (e.g., Manzolli et al, 2022 ;Zhang and Lei, 2010 ;Enríquez-Acevedo et al, 2018 ;Nielsen-Pincus et al, 2017 ). Hence, identifying how locals understand their environmental context provides valuable insights into ecological systems and how communities understand positive or negative environmental interactions with them ( Lemahieu et al, 2018 ).…”
Section: Community Perceptions Of the Swamp Ecosystemmentioning
confidence: 99%